Assembleia de classe como evento de letramento: entrelaçando saberes e fazeres - Cabral, Adriana Hanayá Ferreira (2018)
The need for resignification in the Portuguese Language Teaching process has been leading teachers from basic education to seek new educational practices. An alternative comes from those that are developed in the literacy projects (KLEIMAN, 2000). In this sense, this intervention research aims to study the class assemblies as a literacy event. In order to investigate the effectiveness of assemblies for the resignification related to students’ reading, writing and orality practices of a public school in Rio Grande do Norte, we have postulated the following specific objectives: (i) to identify the developed activities in the class assembly that support the resignification of reading, writing and oral practices; (ii) to investigate how reading, writing and oral activities are developed in a class assembly, focused on action and social change. For this, we have based this research on the dialogical perspective of language from the Circle of Bakhtin (BAKHTIN / VOLOCHÍNOV [1929] 2006); in the literature studies (KLEIMAN, 1995, 2000, 2005, 2006; OLIVEIRA; TINOCO; SANTOS, 2011; STREET, 1984; TINOCO, 2008), in the concepts of learning community (AFONSO, 2001) and the class assembly, also viewed as a literacy event. Concerning to the methodological point of view, we are anchored in the qualitative-interpretative work of an ethnographic dimension connected to Applied Linguistics (MOITA LOPES, 2006). Collaborating in this research, there were 7th grade students, some teachers, the school staff, parents of the students and agents from outside the school community. For the data analysis, we would like to highlight how the class assembly is configured as a literacy event, constituting a space of resignification for reading, writing and oral practices, where the social actions are deliberate, and enable the students' empowerment, and the transformation of a state of things from the collective action.